Ownership structures and effects of related lending and loan guarantees on firm performance in business groups - Yogesh, Maheshwari; Pankaj, Gupta (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study identifies a sample of listed Indian business group firms, which exhibit an increasing trend in leverage, related lending and loan guarantees. Business groups in India, primarily adopt pyramidal structure in which decision making is done through control rights approach. The paper examines the ownership structures in business groups and studies the effects of related lending and loan guarantees on firm performance in such business groups through a panel data regression with fixed effects. The regression results suggest that lending and loan guarantees to related parties affect the operating performance of group firms positively. The relationship has been found to be significant for most of the categories of business groups studied for the two measures of firm performance, namely gross profit to asset ratio and return on assets. However, their effect on market value is found to be negative, leading to an inference that such deals are taken adversely by the market.